Comparative study of extraction and characterization of avocado oil, through processes of: thermobeating, enzymatic, hydraulic pressing and expeller. - Alulema Cuesta, Miroslav Gonzalo; Estrada Gaybor, Joselin Patricia; Morocho Salazar, Kenia Doménicka (Ingeniería Química y Desarrollo, 2024)
Avocado (Persea Americana Mill.) is a raw material rich in oil, which is why its extraction and production can be considered an industrial option, since it is attributed several beneficial properties for health. The objective of this work was to carry out a comparative study to obtain avocado oil, Hass variety, by four different methods (thermobeating, enzymatic, hydraulic pressing and expeller), specifying significant differences and determining the best method in terms of performance and quality. The performance variable was calculated on a dry basis, with the Thermobeating method having the highest percentage with 89.78%. Physicochemical tests such as humidity, density, acidity index, peroxide index, saponification index and iodine index were carried out on the oil samples obtained, obtaining the best results in the thermobeating method, with the exception of the peroxide index and whose values were: 0.054%, 0.9039 g/mL, 3.13 g/100g, 78.87 meqO2/kg, 190.06 mkOH/mg, 84.56cg/g respectively. On the other hand, regarding the composition of fatty acids, High Pressure Liquid Chromatography (HPLC) was carried out, where the hydraulic pressing method generated the best values, which were: 23.57 g/100g, 64.29 g/100g, 12.14 g/100g. 100g, 0.48 g/100g, 11.65 g/100g, 61.07 g/100g, 21.00 g/100g and 1.26 g/100g for Saturated, Monounsaturated, Polyunsaturated Fatty Acids, Omega 3, 6, 9, Palmitic Acid and Stearic Acid, respectively. Finally, these values were contrasted with experimental data from other investigations together with those of a commercial oil, finding values close to those reported.
Keywords: Avocado; hermobeating; enzymatic; hydraulic pressing; expeller pressing; high pressure liquid chromatography (HPLC); fatty acids